Genome-Wide Association Analysis of Young-Onset Stroke Identifies a Locus on Chromosome 10q25 Near HABP2. Issue 2 (February 2016) - Cheng, Yu-Ching; Stanne, Tara M.; Giese, Anne-Katrin; Ho, Weang Kee; Traylor, Matthew; Amouyel, Philippe; Holliday, Elizabeth G.; Malik, Rainer; Xu, Huichun; Kittner, Steven J.; Cole, John W.; O'Connell, Jeffrey R.; et al.
Abstract : Background and Purpose—: Although a genetic contribution to ischemic stroke is well recognized, only a handful of stroke loci have been identified by large-scale genetic association studies to date. Hypothesizing that genetic effects might be stronger for early- versus late-onset stroke, we conducted a 2-stage meta-analysis of genome-wide association studies, focusing on stroke cases with an age of onset <60 years. Methods—: The discovery stage of our genome-wide association studies included 4505 cases and 21 968 controls of European, South-Asian, and African ancestry, drawn from 6 studies. In Stage 2, we selected the lead genetic variants at loci with association P <5×10 −6 and performed in silico association analyses in an independent sample of ⩽1003 cases and 7745 controls. Results—: One stroke susceptibility locus at 10q25 reached genome-wide significance in the combined analysis of all samples from the discovery and follow-up stages (rs11196288; odds ratio =1.41; P =9.5×10 −9 ). The associated locus is in an intergenic region between TCF7L2 and HABP2 . In a further analysis in an independent sample, we found that 2 single nucleotide polymorphisms in high linkage disequilibrium with rs11196288 were significantly associated with total plasma factor VII–activating protease levels, a product of HABP2 . Conclusions—: HABP2, which encodes an extracellular serine protease involved in coagulation, fibrinolysis, and inflammatory pathways, may be a genetic susceptibility locus for early-onset stroke. Abstract : Supplemental Digital Content is available in the text.